The effect of technological, organizational and environmental factors on artificial intelligence adoption among Malaysia MSMEs: A preliminary analysis - Salleh Hudin, Norlaile; Ramdan, Mohamad Rohieszan; Abd. Hadi, Fatimah Salwa; Bunsit, Thanawit; Ahmad, Nur Shahira; Jingcheng, Sun (Journal of Islamic, Social, Economics and Development, 2025)
This is a preliminary study aims to determine the effect of technological, organizational and environmental factors on artificial intelligence (AI) adoption among Malaysia MSMEs. This study embarks on the Technology-Organization-Environment (TOE) framework. Using a questionnaire adopted from a previous study, this study obtains 34 responses from MSMEs in Malaysia which have been selected using convenience sampling. Data are tested using correlation and multiple regression analysis. Findings show a significant correlation between organizational and environmental factors with AI adoption at a significant level of 0.05. Moreover, the multiple regression analysis reveals that the model is statistically significant and explains the variation in AI adoption by 18.8%. However, organizational factor is the only predictor that has a significant positive effect on AI adoption, implying that top management support towards AI trainings to increase employees’ awareness and readiness are critical for successful AI adoption in MSMEs. Therefore, this study provides valuable preliminary insights to Malaysian policymakers and companies on how to enhance AI adoption among Malaysia MSMEs for the future economic growth.